Integrative transcriptomic and TMT-based proteomic analysis reveals the mechanism by which AtENO2 affects seed germination under salt stress - Wu, Yu; Liu, Huimin; Bing, Jie; Zhang, Genfa (Frontiers in Plant Science, 2022)
Seed germination is critical for plant survival and agricultural production and is affected by many cues, including internal factors and external environmental conditions. As a key enzyme in glycolysis, enolase 2 (ENO2) also plays a vital role in plant growth and abiotic stress responses. In our research, we found that the seed germination rate was lower in the AtENO2 mutation (eno2-) than in the wild type (WT) under salt stress in Arabidopsis thaliana, while there was no significant difference under normal conditions. However, the mechanisms by which AtENO2 regulates seed germination under salt stress remain limited. In the current study, transcriptome and proteome analyses were used to compare eno2- and the WT under normal and salt stress conditions at the germination stage. There were 417 and 4442 differentially expressed genes (DEGs) identified by transcriptome, and 302 and 1929 differentially expressed proteins (DEPs) qualified by proteome under normal and salt stress conditions, respectively. The combined analysis found abundant DEGs and DEPs related to stresses and hydrogen peroxide removal were highly down-regulated in eno2-. In addition, several DEGs and DEPs encoding phytohormone transduction pathways were identified, and the DEGs and DEPs related to ABA signaling were relatively greatly up-regulated in eno2-. Moreover, we constructed an interactive network and further identified GAPA1 and GAPB that could interact with AtENO2, which may explain the function of AtENO2 under salt stress during seed germination. Together, our results reveal that under salt stress, AtENO2 mainly affects the expression of genes and proteins related to the phytohormone signal transduction pathways, stress response factors, and reactive oxygen species (ROS), and then affects seed germination. Our study lays the foundation for further exploration of the molecular function of AtENO2 under salt stress at the seed germination stage in Arabidopsis thaliana.